Attitude of Hearing Impaired Students Towards Assistive Technology Utilization in Oyo State Adopting the Survey Method - Aderonke Kofo Soetan; Amos Ochayi Onojah; Tawakalit Bukola Alaka; Adenike Aderogba Onojah (Indonesian Journal of Community and Special Needs Education, 2021)
This study examined attitude of hearing-impaired students towards assistive technology utilization for learning and its gender’ influence. The study adopted the descriptive research type. mean and t-test were used for the research. The findings established that Students with hearing impairments were enthusiastic about using hearing assistive equipment in the classroom. This implies that positive attitude of students towards the use of the assistive technologies will influence their utilization of such technologies for learning. As a result, it was however recommended that schools hire Educational Technologists who can help with the appropriate use of assistive technology tools to enhance classroom instruction.